Stiff reconfigurable polygons for smart connecters and deployable structures. (October 2019) - Zhao, Zeang; Wang, Ke; Zhang, Lu; Wang, Li-Chen; Song, Wei-Li; Fang, Daining
Highlights: Proposed a type of reconfigurable polygon structure that is reconfigurable, remote controllable and stiff during the actuation process. Established several design methods of the reconfigurable polygons including parametrical design and assemblage design. Potential applications of the reconfigurable polygons in frame connections and deployable structures are exhibited both experimentally and theoretically. Abstract: Reconfigurable structure possesses the ability to transfer its shape and functionality on demand, which has inspired wide applications in load-bearing frames, mechanical metamaterials and soft robots. However, constrained by material systems and actuation methods, present reconfigurable structures exhibit apparent contradiction between the actuation performance and structural stiffness. That is, structures with considerable actuated deformation always become incapable of load bearing, and vice versa. In this paper, we propose a reversible and remote controllable reconfigurable structure that remains stiff during the actuation process. Our method combines stiff shape memory alloy actuators together with the structural design of 3D printed reconfigurable element. Upon actuation, considerable deformation is obtained without losing the load bearing capability. The actuation space of the reconfigurable structure can be programmed by designing geometrical parameters as well as the arrange and assembly of different elements. Potential applications of the reconfigurable element and reconfigurable assemblage in frame connections and deployable structures are investigated both experimentally and theoretically.